Experiences of women who have completed a job skills training programme and their ability to access employment opportunities - Simanga, Olga (Department of Social Development, 2020)
Women make up more than half the population of South Africa. Despite the countries’ legislation and policies to promote the rights and social position of women, many remain unemployed and disempowered, face ongoing discrimination and are not able to access resources including educational opportunities. This dissertation reports on the outcomes of a study that was conducted with women to assess their ability to access employment opportunities after having completed a skills training program. In-depth, face-to-face interviews were undertaken with fifteen women who were purposively selected from different backgrounds of Cape Town who had participated in a skills training program to participate in the research. The research integrated a qualitative exploratory approach to explore various experiences of the participants to examine how their involvement with a job skills training programme enabled them to access employment. The research findings revealed that the job skills training programmes enabled most of the women to get employment, and as a result, be able to support themselves financially. Their sense of wellbeing improved, and they were able to access resources like housing. The study also found that policies such as the Employment Equality Act No. 55 of 1998 was well understood and implemented by organisations promoting women’s empowerment through skills training and they implemented the policy to improve the lives of women. However, the study also found existing challenges for women related to the implications of past discriminatory policies and cultural dimensions of family life, especially within black communities, by which women’s role were understood as having to be in the home. The research concludes with recommendations that include further education in communities as well as working spaces about women’s empowerment for both men and women, better enforcement of the rights of women by the state, and further research on how to address the challenges that women face in South Africa society as relates their empowerment.